Factors Influencing Consumers’ Decision to Order Food via the GrabFood Application in Nong Khang Phlu Subdistrict, Nong Khaem District, Bangkok - ตรีวิจิตร วรเทพ; ชูเชิด พีรพล; หน่อแสง สามหลวง; ตันติศิริเจริญ กชกานต์; อบเชย อัคครเดช; ฉิมมณี ชลธิชา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) examine the factors influencing consumers’ decisions to use the GrabFood application in Nong Khang Phlu Subdistrict, Nong Khaem District, Bangkok, and 2) compare decision-making behavior classified by demographic factors, including gender, age, marital status, education level, occupation, and income. The sample consisted of 400 respondents. A questionnaire was used as the data collection instrument, and the data were analyzed using descriptive and inferential statistics. The findings revealed that: 1) The marketing mix factors (7Ps) that significantly influenced the decision to use the service at the 0.05 level were product, price, and people. Meanwhile, place (distribution channel), promotion, process, and physical evidence showed no statistically significant influence. 2) When comparing demographic factors, age, occupation, and monthly income significantly affected consumers’ decisions at the 0.05 level. In contrast, gender, education level, and marital status showed no statistically significant differences.